Thermoelasticity in Ge due to nonuniform distribution of doping impurity studied by light polarization modulation technique - Serdega, B.K.; Venger, Ye.F.; Nikitenko, Ye.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Volume-gradient photovoltage and birefrigence caused by a difference of main mechanical stress components have been studied in the Ge-monocrystal with step-like distribution of the doping impurity concentration, N. The qualitative agreement between the function obtained by integration of the spatial dependence of the anisotropy and of the coordinate dependence of the photovoltage was observed. Using this fact, the conclusion is made that the features of thermoelastic mechanical stress can be distribution of expressed by the dependence |σz - σy| ~ d²N/dz². Remove selected